LITERASI DIGITAL DALAM PEMBELAJARAN DARING - Karsoni Berta Dinata (Eksponen, 2021)
The success of online learning is determined by several aspects, namely aspects of facilities and infrastructure as well as aspects of the ability of lecturers and students in organizing online learning. This article aims to examine the role of digital literacy in online learning. Based on the results of the study, it can be concluded that digital literacy skills have an important role in online learning. Students with good digital literacy skills will strive to find and select important information and understand, communicate, and convey ideas in the digital space. In addition, digital literacy skills will open opportunities for students to think, communicate, and work which ultimately leads to student learning success.